Nutritional value of common edible reptiles - Mail, Joycelyn Anak (University Malaysia Sarawak, UNIMAS., 2013)
The study is focused on the nutritional value of common edible reptile’s meat and effects of consuming the meat toward human. The parameters for the analysis are moisture analysis, crude protein analysis, and crude fat analysis by using proximate analysis method. Proximate analysis is the method to determine the chemical constituents of feedstuff by follow the normal composition parameter of the feed. The samples that are used for the analysis are Python reticulatus, Cuora amboinensis, Crocodylus porosus, Dogania subplana, Varanus salvator, Acrochordus javanicus and Xenelaphis hexagonotus. The native people in Padawan and Serian area commonly consume the reptiles’ meat because of the taste of the flesh instead of knowing the actual nutritional value of the meat. Based on the analysis, reptiles’ meats have not met the standard human nutrients requirement. Besides that, the conservation of the wild animal is taken seriously by Sarawak Forestry Department where some of the species are listed in Sarawak Wildlife Protection Ordinance, 1998.